Aspekte van die voorsiening van oop ruimtes by metropolitaanse beplanning - Claassen, PE (Town and Regional Planning, 1975)
The appointment of Metropolitan Guide Board Committees by the Minister of Planning, and especially the prospect of legal powers that will be created by the Physical Planning Amendment Bill currently in front of Parliament, has sparked new hopes from planners that the long-awaited metropolitan planning will now take place. *This article is written in Afrikaans.